2009
DOI: 10.1038/ejcn.2009.102
|View full text |Cite
|
Sign up to set email alerts
|

Energy density of foods, but not beverages, is positively associated with body mass index in adult women

Abstract: Background/Objectives Energy density (kJ/g) may have a strong influence on energy balance. Although beverages are a considerable source of energy in the US diet, rarely have studies among free-living populations investigated the energy density of foods (EDF) and the energy density of beverages (EDB) simultaneously. We examined the independent simultaneous associations of EDF and EDB on energy intake and Body Mass Index (BMI) in adult women. Subjects/Methods This cross-sectional design focused on 348 elementa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 38 publications
1
29
0
Order By: Relevance
“…We have previously reported that obese individuals in this sample consumed more kilocalories and energy from fat that those who were normal weight and that only 7% of the sample met the My Pyramid recommendations for fruits and vegetables 25 . Further, we showed that the individuals in the highest tertile for energy density of food consumed had higher BMI that those in the lowest tertile 26 . Some 2.2 of the meals and snacks per day were eaten at school and this accounts for 37% of the daily energy 27 .…”
Section: Discussionsupporting
confidence: 51%
“…We have previously reported that obese individuals in this sample consumed more kilocalories and energy from fat that those who were normal weight and that only 7% of the sample met the My Pyramid recommendations for fruits and vegetables 25 . Further, we showed that the individuals in the highest tertile for energy density of food consumed had higher BMI that those in the lowest tertile 26 . Some 2.2 of the meals and snacks per day were eaten at school and this accounts for 37% of the daily energy 27 .…”
Section: Discussionsupporting
confidence: 51%
“…This meant that it was not possible to use exactly the same method as previously published studies (e.g. classifying liquids consumed as foods or added to foods such as smoothies and milk on cereal) as part of food categories (Hartline‐Grafton et al ., ). Further to reviewing the literature and examining the EFS/LCF data, it was considered feasible to use HH and eating out purchases of foods and drinks to calculate ED using five different methods (Table ) after appropriate adjustment for waste and weight increase or loss as a result of cooking or dilution.…”
Section: Methodsmentioning
confidence: 97%
“…Hartline‐Grafton et al . () reported that ED from food was related to BMI. However, their definition of food included liquids consumed as foods (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…47) or confounding factors (20). The rodent studies have been performed using low-fat (ϳ10% kcal fat) diets, which are healthier than diets with a high-fat (HF) content (11). In contrast to low-fat diets, HF diets induce obesity and insulin resistance in mouse strains sensitive to development of dietinduced obesity, such as C57BL/6J (9).Therefore, we previously studied the effects of differences in GI (LGI vs. HGI) in the context of an HF (30% kcal fat) diet, rather than a low-fat diet, in obesity-prone C57BL/6J adult male mice (43).…”
mentioning
confidence: 99%